Garvey's choice : the graphic novel - Grimes, Nikki (Wordsong, an imprint of Astra Books for Young Readers, 2023)
"Award-winning author Nikki Grimes's beloved novel in verse Garvey's Choice is now a graphic novel, imaginatively and dramatically illustrated by Little Shaq artist Theodore Taylor III"--